2022
DOI: 10.1155/2022/5029663
|View full text |Cite|
|
Sign up to set email alerts
|

The Wearable Lower Limb Rehabilitation Exoskeleton Kinematic Analysis and Simulation

Abstract: In recent years, due to the increase in the incidence of traffic accidents, the number of people with limb injuries has also increased. At the same time, among the aging population, neurological diseases or cardiovascular and cerebrovascular diseases have caused many people to have limb hemiplegia. It has been clinically proven that the use of rehabilitation equipment can help patients with limb injuries to restore limb motor function. This paper takes wearable lower limb rehabilitation exoskeleton as the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, their study did not include validation for the kinematic analysis. Li et al [25] conducted an analysis of both forward and inverse kinematics for a three-DOF LLE. They simulated the LLE using ADAMS ™ ; however, their findings lacked subsequent kinematic validation.…”
Section: Introductionmentioning
confidence: 99%
“…However, their study did not include validation for the kinematic analysis. Li et al [25] conducted an analysis of both forward and inverse kinematics for a three-DOF LLE. They simulated the LLE using ADAMS ™ ; however, their findings lacked subsequent kinematic validation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rotor of the motor and the rotation center of the knee joint cannot overlap in real time, resulting in poor experience and rehabilitation effect [10,11]. To improve the comfort of patients during the rehabilitation process, a lower limb exoskeleton for the knee joint motion with two degrees of freedom was designed in [12].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%